1996
DOI: 10.4098/at.arch.96-2
|View full text |Cite
|
Sign up to set email alerts
|

Space use and juvenile recruitment in gray-tailed volves in response to intruder pressure and food abundance

Abstract: Wolff J. O. and Schauber E. M. 1996. Space use and juvenile recruitment in gray-tailed voles in response to intruder pressure and food abundance. Acta Theriologica 41: 35-43.We examined space use by female gray-tailed voles Microtus canicaudus (Miller, 1897) and recruitment of juveniles in response to relative abundance of food and increased intruder pressure following experimental removal of habitat. Our experiment indirectly tested the assumptions of the food-defense and pup-defense hypotheses for female t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…gapperi, Clulow et al 1982). Infanticide by unfamiliar females and/or males is also suggested in other small rodents (Wolff and Cicirello 1991;Lambin and Krebs 1993;Mappes et al 1995;Wolff and Schauber 1996;Wolff 1997;Lambin and Yoccoz 1998). However, the influence of dispersers on the reproduction and survival of resident individuals is unknown in the gray-sided vole.…”
Section: Density and Dispersalmentioning
confidence: 99%
“…gapperi, Clulow et al 1982). Infanticide by unfamiliar females and/or males is also suggested in other small rodents (Wolff and Cicirello 1991;Lambin and Krebs 1993;Mappes et al 1995;Wolff and Schauber 1996;Wolff 1997;Lambin and Yoccoz 1998). However, the influence of dispersers on the reproduction and survival of resident individuals is unknown in the gray-sided vole.…”
Section: Density and Dispersalmentioning
confidence: 99%
“…Consequently, the females' time available for mate choice should be highly constrained by the tradeoff between the time and energy spent on finding a new mate, nursing and protecting their offspring (Klemme et al 2006). In species with a promiscuous-polygynous mating system, females display intrasexual territorial behaviour to protect nestlings from infanticidal females, since males rarely commit infanticide (Wolff 1993;Wolff and Schauber 1996;Wolff and Peterson 1998;Bond and Wolff 1999;Getz et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been difficult to demonstrate experimentally that food shortage is a sufficient factor in limiting reproduction or population growth in rodents. Studies with several species of Microtus in enclosures have shown that populations typically reach 2-10-times higher densities than in unenclosed populations (Wolff & Schauber 1996;Wolff & Sherman 2007). These results suggest that normal dispersal, predation and other factors limit population growth before food resources are exhausted.…”
Section: Is Food a Defensible Resource?mentioning
confidence: 99%